The clinical features, prognostic significance, and immune heterogeneity of CD37 in diffuse gliomas - Xuejun Yan (Elsevier, 2021)
Summary: Diffuse glioma is the most prevalent and malignant brain tumor. The function and significance of CD37 in diffuse gliomas remain largely unknown. Here, we showed CD37 was abnormally expressed in diverse cancers, especially glioma by pan-cancer differential expression analysis. In addition, we found CD37 was upregulated in higher grade and IDH or IDH1-wildtype gliomas, which was further validated by qPCR and IHC. Survival analysis revealed CD37 served as an independent indicator for unfavorable prognosis of patients with diffuse gliomas. Functional enrichment analysis revealed CD37 was associated with immunological processes. Moreover, immune infiltration analyses suggested gliomas with high-expression CD37 had greater infiltration of M2 macrophages and neutrophils, and lower NK cell abundance. CD37 was closely correlated to immune checkpoint molecules, including CD276, CD80, CD86, and PD-L2. Our results indicated CD37 is an independent prognostic factor and plays an immunosuppressive role in diffuse gliomas. Targeting CD37 could be a promising immunotherapeutic strategy for diffuse gliomas.